Jogos como recurso didático para o ensino da língua inglesa e sua adaptação para alunos com deficiência visual - Alves, Elizete Oliveira (Universidade Federal de São Carlos, 2026)
This research looks at the process of analyzing and adapting games as teaching tools for English language instruction in middle school. This resource comes up as a low-cost, non-digital alternative to boost student motivation. The main goal is to present and analyze the theoretical and methodological aspects of four original games, focusing on accessibility for students with visual impairments. It's a qualitative study, with document analysis and a descriptive-interpretative approach, motivated by the practical challenge of including a blind student in playful activities supported by analog games. The research is based on the principles of inclusive education, Universal Design for Learning (UDL), and the theoretical contributions of John Dewey and James Paul Gee. Based on a reflective analysis of the pedagogical design of the developed games, the study discusses how their tactile features, in braille, the use of enlarged fonts and contrasting colors, along with the collaborative development of an offline digital app prototype designed as an adaptation tool for one of the games, provide structural conditions to support participation and meaningful learning in inclusive English teaching contexts. The study was developed from the teaching experience of the teacher-researcher in public school classrooms, considering specific accessibility needs observed in the school context, especially in serving students who are blind or have low vision. As an educational product, a practical guide was created to support pedagogical activities, helping English teachers use and adapt the games. It is concluded that the combination of playfulness, accessibility, and language teaching can help build more democratic and inclusive teaching practices, providing support for teacher training and for the development of low-cost educational materials aimed at the reality of Brazilian public schools.
Games as a teaching tool for English language learning and their adaptation for students with visual impairments
Keywords: Jogos; Ensino de inglês; Deficiência visual; Desenho Universal para a Aprendizagem; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade